Life, Death and Representation Some New Work on Roman Sarcophagi - Elsner, Jas; Huskinson, Janet (Millennium-Studien / Millennium Studies, 2010)
The volume presents essays on different aspects of Roman sarcophagi. These varied approaches produce freshinsights into a subject which has received increased interest in English-language scholarship, with a new awareness of the important contribution that sarcophagi can make to the study of the social use and production of Roman art. Metropolitan sarcophagi are the main focus of the volume, which will cover a wide time range from the first century AD to post classical periods (including early Christian sarcophagi and post-classical reception). Other papers will look at aspects of viewing and representation, iconography, and marble analysis.